2020
DOI: 10.1002/ange.202007548
|View full text |Cite
|
Sign up to set email alerts
|

Radical‐Cation Cascade to Aryltetralin Cyclic Ether Lignans Under Visible‐Light Photoredox Catalysis

Abstract: The development of concise, sustainable, and cost‐effective synthesis of aryltetralin lignans, bearing either a fused lactone or cyclic ether, is of significant medicinal importance. Reported is that in the presence of Fukuzumi's acridinium salt under blue LED irradiation, functionalized dicinnamyl ether derivatives are converted into aryltetralin cyclic ether lignans with concurrent generation of three stereocenters in good to high yields with up to 20:1 diastereoselectivity. Oxidation of an alkene to the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…3c). Treatment of the known tricyclic compound 18a whose relative stereochemistry has been determined by X-ray crystallographic analysis 36 under standard conditions with an excess of MeOH (8.0 equiv) afforded the same products 20a as a mixture of two diastereomers 38 . The reaction proceeded much slower presumably due to the sluggish oxidation of the benzylic carbon of compound 18a, but the diastereoselectivity of this reaction (dr = 4.5:1) was higher than the one-pot process from 17a and MeOH.…”
Section: Articlementioning
confidence: 99%
See 3 more Smart Citations
“…3c). Treatment of the known tricyclic compound 18a whose relative stereochemistry has been determined by X-ray crystallographic analysis 36 under standard conditions with an excess of MeOH (8.0 equiv) afforded the same products 20a as a mixture of two diastereomers 38 . The reaction proceeded much slower presumably due to the sluggish oxidation of the benzylic carbon of compound 18a, but the diastereoselectivity of this reaction (dr = 4.5:1) was higher than the one-pot process from 17a and MeOH.…”
Section: Articlementioning
confidence: 99%
“…Most of the aryltetralin cyclic ether lignans bear multiple alkoxyl or hydroxyl substituents on the aromatic rings with a trans-fused B/C ring system. We have previously shown that the stereochemical outcome of the formal [4 + 2] cycloaddition of dicinnamyl ether derivatives under photoredox catalytic conditions depends on the number of hydroxyl/alkoxyl groups on the aromatic rings 36 . The reaction of di(p-methoxy)cinnamyl ether 17a afforded the tricyclic lignan with a cis-fused B/C ring 18, while those derived from polymethoxylated cinnamic alcohols provided the trans-fused B/C ring system 19 (cf Fig.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…The aryltetralin cyclic ether lignans ( Xiang et al., 2020 ), namely, isoshonanin and gaultherin C have been synthesized by Zhu and co-workers from monolignols in three steps in the presence of Fukuzumi's acridinium salt under blue LED irradiation ( Scheme 1 C). The obtained members of this family of natural products display analgetic and anti-inflammatory properties.…”
Section: Construction Of Natural Products From Potentially Lignin-dermentioning
confidence: 99%